The Effect of Brain Training Game activities on Improvement of Cognitive Function measured by Montreal Cognitive Assesment Indonesia version (MoCA-Ina) - Mochamad Bahrudin; Adni Pratiwi; Anang Bayu Seta; Risma Karlina Prabawati (Saintika Medika, 2022)
The function of cognition in young adults (around the age of 20 years) mostly does not develop to its peak, even though at that age a person needs better cognitive abilities to deal with the lectures. Brain training game activities by playing games through the NeuronationTM application can improve cognitive function. To determine the effect of Brain training activities on improvement of cognitive function. Experimental study with two group pre and post design. 74 Sample were medical students of Faculty of Medicine, University of Muhammadiyah Malang class of 2017-2018, divided into control and treatment groups of 37 samples each. The treatment group was given by game brain game training 30 minutes a day, 20 times in 4 weeks.. Cognitive function was measured by the MoCA-Ina test in the control group and pre and post test. The hypothesis test used the pairet samples test. Cognitive function of pre and post test of the control group good cognitive function increased 2.69% and cognitive function of pre and post test of treatment group increased 58.8% with the result of pairet sample analysis of significant p = 0,000 which means that in the control group there was a tendency for increased function cognition after treatment (post test) but the improvement was not significant. In the treatment group with brain training activities cognitive function increased sharply and statistically significant, Brain training activities affect the improvement of cognitive function.